2023
DOI: 10.1002/cncr.34804
|View full text |Cite
|
Sign up to set email alerts
|

Detection of multiple types of cancer driver mutations using targeted RNA sequencing in non–small cell lung cancer

Abstract: Background: DNA-based next-generation sequencing has been widely used in the selection of target therapies for patients with nonsmall cell lung cancer (NSCLC).RNA-based next-generation sequencing has been proven to be valuable in detecting fusion and exon-skipping mutations and is recommended by National Comprehensive Cancer Network guidelines for these mutation types. Methods:The authors developed an RNA-based hybridization panel targeting actionable driver oncogenes in solid tumors. Experimental and bioinfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, on the other hand, two samples with positive results by DNA-NGS, failed to have RNA-NGS results due to insufficient RNA quality, indicating the higher sample quality requirements of RNA-NGS. Another study conducted head-to-head comparison of DNA-NGS and RNA-NGS in clinical formalin fixed paraffin embedded (FFPE) samples of 1253 NSCLC patients and found that 6% (10/ 168) of patients with negative results of DNA-NGS oncogenic drivers test were rediscovered by RNA-NGS detection (including 7 samples of fusion mutations, 3 samples of MET exon 14 skipping mutations), and these patients were offered targeted therapy [23].…”
Section: Level Of Evidence: Moderate Strength Of Recommendation: Mode...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, on the other hand, two samples with positive results by DNA-NGS, failed to have RNA-NGS results due to insufficient RNA quality, indicating the higher sample quality requirements of RNA-NGS. Another study conducted head-to-head comparison of DNA-NGS and RNA-NGS in clinical formalin fixed paraffin embedded (FFPE) samples of 1253 NSCLC patients and found that 6% (10/ 168) of patients with negative results of DNA-NGS oncogenic drivers test were rediscovered by RNA-NGS detection (including 7 samples of fusion mutations, 3 samples of MET exon 14 skipping mutations), and these patients were offered targeted therapy [23].…”
Section: Level Of Evidence: Moderate Strength Of Recommendation: Mode...mentioning
confidence: 99%
“…Using an NGS panel composed of a specific number of genes, typically covering at least 50 genes, is a feasible strategy. If no oncogenic drivers are detected by a DNA-based NGS panel, RNA-based NGS should be considered [23]. In addition to considering the number of genes, it is also important to consider the tiers of somatic variants on the Level of evidence: strong Strength of recommendation: strong In the mid-1990s, with the development of imaging and radiology the multidisciplinary team (MDT) model was established and started to flourish due to its patientcentered core as well as the consequent improved clinical treatment decision.…”
Section: Level Of Evidence: Moderate Strength Of Recommendation: Mode...mentioning
confidence: 99%
“…In the article in this issue of Cancer by Ju and colleagues, both DNA-based and RNA-based NGS were performed separately with nucleic acid extracted from the same formalin-fixed, paraffinembedded NSCLC samples (N = 1253). 5 Their RNA-based panel covered 30 genes associated with clinically significant fusions plus six housekeeping genes. Because of the fusion-oriented design, some genes with clinically important mutations, such as ERBB2 and KRAS, were not included.…”
mentioning
confidence: 99%